Fiscal policy and aggregate demand: Reply - Aschauer, David Alan (American Economic Review, 1993)
There appear to be two main conclusions of Fred C. Graham's paper. First, he argues that the empirical evidence in Aschauer (1985) supporting the permanent-income hypothesis and a significant degree of substitutability between private consumption and government spending is specific to the sample period and to the nature of [Aschauer's] 'unrestricted' alternative (Graham, 1993 p. 666). Second, after disaggregating government spending into various components he finds limited support for the hypothesis that federal nondefense spending-as opposed to total federal, state, and local spending-substitutes for private consumption. The focus of my 1985 paper was on deriving a test of the Ricardian equivalence theorem within an Euler-equation framework. Graham seems to have missed this point. Indeed, there is no evidence in his paper to support the Keynesian view that tax cuts stimulate private consumption and aggregate demand. Admittedly, Graham finds that changes in disposable income lead to changes in private consumption; but this is not enough to support the standard Keynesian analysis. Specifically, it is necessary to determine whether tax changes per se induce changes in consumption spending. Consider a model similar to Graham's equation (4), namely,